Investigating the shape of the EKC: A nonparametric approach - Giovanni Baiocchi; Salvatore DiFalco (Fondazione Eni Enrico Mattei (FEEM), 2001)
In this paper we investigate the existence and shape of the Environmental Kuznets Curve (EKC) by means of nonparametric methods. We also investigate the issues involved in the choice of nonparametric estimator. We find that the nature of the economic relationship and the quality of environmental data can considerably impact estimates and therefore the implied policy recommendations. The flexible nature of nonparametric estimation allows us to develop a nonparametric test in the spirit of Silverman's (1981) bootstrap test to test whether the Kuznets curve exists and what shape it takes. We also estimate the nonparametric elasticity with respect of per capita income. We find evidence of asymmetric behaviour of the curve before and after the turning point.
Keywords: Q25; Q32; 330; Environmental Kuznets Curve; nonparametric methods; Umweltbelastung; Wirtschaftswachstum; Schätzung; Welt; Environmental Kuznets Curve